Model Peningkatan Minat Belajar Melalui Penerapan Strategi Role Playing Kolaborasi Active Debate Dalam Proses Pembelajaran Pendidikan Kewarganegaraan Pada Siswa Kelas Viii Smp Prawira Marta Kabupaten Sukoharjo TahunPelajaran 2015/2016 - Trismantyasi, Rejeki; , Drs. Yulianto Bambang Setyadi, M.Si (2016)
This study aims to increase interest in learning in the learning process Citizenship Education at Butler Junior High School eighth grade students Marta Sukoharjo 2015/2016 school year by implementing a collaboration strategy Active Role Playing Debate. Learning interest of the students was very low before the given test models and teachers are seeking alternative solutions, such as: using the method varied lectures, discussions, explaining material is not too much and assignments. The result of the application of learning strategy has not been able to increase student interest. The solution offered in this research is through the implementation of a strategy of collaboration Active Role Playing Debate. The implementation of the subject is class VIII SMP Prawira Marta Sukoharjo district in the academic year 2015/2016, amounting to 22 students. The research data were collected through an informant or informants, places and events ongoing learning activities. Data collection techniques by using the method of observation, interviews and questionnaires. This study was conducted in two test models. Hopefully, through the implementation of strategies Active Role Playing Debate collaboration, the results of learning interest in learning Citizenship Education at Butler Junior High School eighth grade students Marta Sukoharjo 2015/2016 academic year can be increased by at least 80% of the 22 students. The results of this study indicate that interest in learning to students in class VIII SMP Prawira Marta Sukoharjo district in the academic year 2015/2016 prior research conducted through the implementation of collaborative strategies Active Role Playing Debate are as many as 10 students (45,46%). Once through the implementation of these strategies, test model I increased to 11 students (50%) and the model II trials increased to 18 students (81,82%).